FOREST MANAGEMENT FOR THE CONSERVATION OF Araucaria angustifolia IN SOUTHERN BRAZIL - Hess, André Felipe Felipe; Loiola, Táscilla; Souza, Isadora Arruda de; Minatti, Myrcia; Ricken, Pollyni; Borsoi, Geedre Adriano (Floresta, 2018)
Forest management is the legal instrument to propose interventions and conservation of tree species in natural forests; it is a requirement for the management of commercial forest plantations. Considering as objective the conservation with sustainable management and knowledge of the increment rates in forests with Araucaria angustifolia, growth models were fitted with the measures of ring increment data of 587 trees, covering all distribution diameter classes, in four sites in southern Brazil. These fitted models showed the minimum cutting diameter of 40 cm for about 20 years (maximum annual increment in volume), cutting diameter of 55 cm in 37 years (maximum annual mean volume increment) and cutting cycle of 2 to 22.5 years for the diameter classes. The current increment rates in these diameter classes showed the need for approximately 20 years for the species to reach the minimum logging diameter. The lower growth rate in smaller diameter classes indicates that the species requires more time to reach the minimum cutting diameter, which is detrimental to the forest structure. The growth rate variability must be considered in the management of forests with A. angustifolia. The results showed the need and viability of sustainable silvicultural interventions to preserve forest diametric structures; otherwise the forest could compromise the development of larger trees.